2011
DOI: 10.1007/s12192-011-0272-8
|View full text |Cite
|
Sign up to set email alerts
|

Heat-shock response and antioxidant defense during air exposure in Patagonian shallow-water limpets from different climatic habitats

Abstract: Climate warming involves not only a rise of air temperature means, but also more frequent heat waves in many regions on earth, and is predicted to intensify physiological stress especially in extremely changeable habitats like the intertidal. We investigated the heat-shock response (HSR) and enzymatic antioxidant defense levels of Patagonian shallow-water limpets, adapted to distinct tidal exposure conditions in the sub-and intertidal. Limpets were sampled in the temperate Northern Patagonia and the subpolar M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 58 publications
0
18
0
3
Order By: Relevance
“…The systemic occurrence of a starved phenotype may not be primarily apparent in the tissues tested in this experiment, especially the hemocytes, as one of the first biochemical symptoms would be mobilization of stored energy reserves, such as fat or protein. In addition, the induction of stress response genes in Antarctic invertebrates is potentially attenuated in Antarctic species compared with comparable temperate invertebrates (see the tiered response of heat shock genes to tidal emersion in Antarctic and Patagonian limpets in Pöhlmann et al 2011).…”
Section: Cross Effects Of Starvation and Injury On Gene Expression Inmentioning
confidence: 99%
“…The systemic occurrence of a starved phenotype may not be primarily apparent in the tissues tested in this experiment, especially the hemocytes, as one of the first biochemical symptoms would be mobilization of stored energy reserves, such as fat or protein. In addition, the induction of stress response genes in Antarctic invertebrates is potentially attenuated in Antarctic species compared with comparable temperate invertebrates (see the tiered response of heat shock genes to tidal emersion in Antarctic and Patagonian limpets in Pöhlmann et al 2011).…”
Section: Cross Effects Of Starvation and Injury On Gene Expression Inmentioning
confidence: 99%
“…However it is worth noting that these species inhabit different shore levels and display different physiological strategies to survive to thermal stress and air exposure during tidal emersion (e.g. Malanga et al, 2004;Pöhlmann et al, 2011). In particular, it has been demonstrated that N. magellanica has a more efficient response to short periods of tidal exposure and enhanced temperatures compared with N. deaurata (Pöhlmann et al, 2011).…”
Section: Sst Sss and D 18 Ow In The Study Areamentioning
confidence: 99%
“…Malanga et al, 2004;Pöhlmann et al, 2011). In particular, it has been demonstrated that N. magellanica has a more efficient response to short periods of tidal exposure and enhanced temperatures compared with N. deaurata (Pöhlmann et al, 2011). Therefore, aforementioned differences could to some extent reflect different specie-specific physiological responses to environmental stress.…”
Section: Sst Sss and D 18 Ow In The Study Areamentioning
confidence: 99%
“…Arial exposure may act as an important factor modulating upper temperature tolerance, as this is a predictable aspect of environmental change in the intertidal zone (Gracey et al 2008;Miller et al 2009;Pöhlmann et al 2011;Connor and Gracey 2012;Bjelde and Todgham 2013;Han et al 2013;Huang et al 2015).…”
Section: Introductionmentioning
confidence: 99%